2018
DOI: 10.1097/sla.0000000000002027
|View full text |Cite
|
Sign up to set email alerts
|

Carolinas Comfort Scale as a Measure of Hernia Repair Quality of Life

Abstract: The present study confirms that the CCS questionnaire is a validated, sensitive, and robust instrument for assessing QOL after hernia repair, which has become a predominant outcome measure in this discipline of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…Therefore, in 2008, Heniford proposed a new, easy-to-use, and reliable tool for evaluating pain in the inguinal region, i.e., the Carolina Comfort Scale. Using this scale, a patient specifies the intensity of pain during eight daily activities, and the scope of the questions in this scale is consistent with the scope of the questions presented to our study group [ 12 ].…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, in 2008, Heniford proposed a new, easy-to-use, and reliable tool for evaluating pain in the inguinal region, i.e., the Carolina Comfort Scale. Using this scale, a patient specifies the intensity of pain during eight daily activities, and the scope of the questions in this scale is consistent with the scope of the questions presented to our study group [ 12 ].…”
Section: Discussionmentioning
confidence: 81%
“…A generic validated QOL scale should be more acceptable to population and observers and should be consistent and acceptable in both short and long term follow up. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Literature review has showed that, it is best to use a generic scale with a disease specific scale along with a validated pain scale that can cover the immediate postoperative period. 8,13,14 Pain scores should be used in the peri-operative period to determine if patient has developed any acute pain or his pre-operative pain is continuing and becoming a chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Time frame for follow up is the most diverged subject in the literature, where quality of life was measured as soon as next day of surgery to up to five years. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] No consistency was found in the follow up period and in different studies it ranges from days to years. Literature review also did not help to conclude the best time for follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unique set of complications arising from VH surgery, the importance of chronic pain and QoL, a hernia-specific patient reported outcome assessment tool, such as the Carolinas Comfort Scale [70] or the EuraHS-QoL questionnaire [69], should be used.…”
Section: Discussionmentioning
confidence: 99%